Surgical gynecology a case-based approach - Jenkins, Todd ca. 20./21. Jh; Keder, Lisa ca. 20./21. Jh; Famuyide, Abimbola ca. 20./21. Jh; Gecsi, Kimberly S. ca. 20./21. Jh; Chelmow, David ca. 20./21. Jh (Cambridge University Press, 2022)
Gynecology is principally an operative specialty and the range of gynecologic procedures managed is constantly expanding due to improved instrumentation and minimally invasive techniques. Covering the entire spectrum of gynecologic surgery through a case-based, digestible format, procedures such as vaginal, transvaginal, hysteroscopic, laparoscopic, robotic, and abdominal procedures are included, as well as common surgical challenges and complications. For each case, a clinical vignette outlines the situation and the clinical context of the patient, followed by a comprehensive discussion of the evidence-based management approach and key teaching points. The decision to operate, contraindications, alternatives to surgery and preoperative counseling is discussed in detail along with the level of care needed for each case. Readers will improve their knowledge base of gynecologic surgery and gain multiple tools to overcome common surgical obstacles
Keywords: Generative organs, Female / Surgery